Biocontrol of post-harvest tomato rot caused by Alternaria arborescens using Torulaspora indica - Bosqueiro, Ariane Silva; Bizarria Jr, Rodolfo [UNESP]; Rosa-Magri, Márcia Maria (Taylor & Francis, 2023)
An important concern in modern agriculture is the production of healthy foods. This has resulted in an increasing number of studies on alternative plant protection strategies such as biological control. Yeasts have received considerable attention as biological control agents against postharvest fungal diseases of fruits and vegetables. Here, we describe the potential of the yeast strain Torulaspora indica as a biological control agent against Alternaria arborescens, causal agent of tomato fruits decay. In vitro and in vivo assays were used to evaluate the interaction of Torulaspora indica (CCA5S55) and Alternaria arborescens (ABS2). This was followed by the evaluation of putative mechanisms controlling fungal development. Our results suggest that the production of volatile compounds and competition for nutrients are putative mechanisms by which T. indica inhibits A. arborescens growth in vitro. The results of in vivo assays indicate a reduction in the number of A. arborescens-induced lesions in tomato fruits in the presence of T. indica.
Keywords: biocontrol; Postharvest; sustainable agriculture; tomato; volatile organic compounds